Opioid-Free Anesthesia in Perioperative Care : Findings From a Swedish Web-Based Survey - Diwan, Salwan; Olausson, Alexander; Andréll, Paulin; Wolf, Axel; Jildenstål, Pether (Pain research & management, 2025)
OBJECTIVES: Opioid-free anesthesia (OFA) is a promising alternative to traditional opioid-based anesthesia. Research indicates that OFA reduces postoperative opioid consumption and related adverse effects while maintaining effective pain control and patient safety. Despite these benefits, clinical adoption of OFA remains limited, possible due to gaps in evidence. To bridge this knowledge gap, a web-based survey was used to assess Swedish healthcare professionals' (HCPs') knowledge, attitudes, and practices regarding OFA, aiming to identify barriers and facilitators for its broader integration into routine anesthesia care. METHODS: A web-based survey was sent to anesthesiology department heads at all university hospitals in Sweden and three randomly selected smaller hospitals. The department heads distributed the survey to anesthesiologists, nurse anesthetists, critical care nurses, and registered nurses involved in intraoperative care. The questionnaire had four sections: demographic data, general questions regarding intraoperative care, specific questions on OFA usage, and an open-ended question. RESULTS: A total of 309 HCPs responded to the survey, corresponding to a response rate of 35%. The majority of respondents (77%) had seven or more years of perioperative experience, 63% were female, and 82% worked at university hospitals. Knowledge about OFA was generally low, with 62% reporting insufficient knowledge, and 14% actively applied OFA. Self-report data demonstrated that anesthesiologists had significantly lower knowledge levels on applying OFA compared to nurse anesthetists and critical care nurses (p < 0.01). However, 85% of all HCPs expressed interest in acquiring additional theoretical knowledge about OFA. Additionally, 87% reported either absent guidelines or uncertainty about their existence, while most (57%) agreed that guidelines supporting the practice of OFA should be introduced at their clinic. CONCLUSION: This survey indicated interest in OFA among Swedish perioperative HCPs while revealing key barriers to implementation, including knowledge gaps and limited guidelines. Addressing these challenges through targeted education and institutional support may facilitate broader OFA adoption, enhancing patient safety and multimodal perioperative pain management.
Copyright © 2025 Salwan Diwan et al. Pain Research and Management published by John Wiley & Sons Ltd.
Keywords: Humans; Sweden; Female; Male; Surveys and Questionnaires; Perioperative Care/methods; Adult; Analgesics, Opioid/therapeutic use; Internet; Middle Aged; Anesthesia/methods; Health Knowledge, Attitudes, Practice; Attitude of Health Personnel